PENDAMPINGAN PROSES PRODUKSI DAN PEMASARAN DIGITAL UMKM KOPI MELATI - Gunawan, Barbara (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The purpose of this service program is that partners can improve product quality, be able to innovate products and also increase product sales. In addition to these goals, it is hoped that Mlati Coffee as a partner of this service can be known more widely so that it can grow Patean Regency. This IT-based routine service activity method is a workshop method in the form of training and mentoring as well as using discussion and counseling methods. The results of the activities: 1) Organized counseling on the use of social media (Facebook and Instagram), 2) Conducted counseling on the use of e-commerce (Shopee and Tokopedia), 3) Installed name signs and banners, and 4) Organized outreach and briefing on product innovation. The limitation in this activity is that service activities only focus on production and marketing. One of the long-term work programs is product innovation for Mlati Kopi MSMEs. It is hoped that the team in the future will be able to provide product innovation from the past so that its implementation can be maximized. After this service, MSME owners are able to manage their potential to improve quality. Therefore, it is expected to pay more attention to the potential for further development.